Lateral Habenula Regulates Cardiovascular Autonomic Responses via the Serotonergic System in Rats - Doan, Tri Huu; Sato, Yuma; Matsumoto, Masayuki; Koganezawa, Tadachika (Frontiers in Neuroscience, 2021)
The lateral habenula (LHb) plays essential roles in behavioral responses to stressful events. Stress is tightly linked to autonomic responses such as cardiovascular responses, yet how the LHb regulates these responses is not well understood. To address this issue, we electrically stimulated the LHb in rats, measured its effects on heart rate (HR) and mean arterial pressure (MAP), and investigated the neural circuits that mediate these LHb-induced cardiovascular responses via the autonomic nervous system. We observed that stimulation of the LHb induced bradycardia and pressor responses, whereas stimulation of the adjacent areas changed neither the HR nor the MAP. Bilateral vagotomy and administration of a muscarinic receptor antagonist suppressed the LHb-stimulation effect on the HR but not on the MAP, whereas administration of a β-adrenoceptor antagonist partly attenuated the effect on the MAP but not on the HR. Thus, the LHb-induced cardiovascular responses of the HR and the MAP were likely caused by activations of the cardiac parasympathetic nerves and the cardiovascular sympathetic nerves, respectively. Furthermore, administration of a nonselective 5-HT receptor antagonist significantly attenuated the LHb-stimulation effects on both the MAP and the HR. A 5-HT2 receptor antagonist also attenuated the LHb-stimulation effects. A low dose of a 5-HT1A receptor antagonist enhanced the LHb-stimulation effects, but a high dose of the drug attenuated them. A 5-HT1B and 5-HT1D receptor antagonist as well as a 5-HT7 receptor antagonist did not affect the LHb-stimulation effects. Taken together, our findings suggest that the LHb regulates autonomic cardiovascular responses at least partly through the serotonergic system, particularly via the 5-HT1A and 5-HT2 receptors.